Regulations in National Laws on Construction in Coastal Areas - Afrough, Abdolmohammad; Mirabbassi, Syed Bagher; Asgarkhani, Abumohammad; Moradi, Maryam (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
The coasts and the sides of the sea, the forehead of the lands and, consequently, are the forefront of the national lands. Our sustained and deep effort in coastal and port management and engineering is a special part of the ethical responsibility of the Ports and Maritime Organization and from this, the fate of the beauty and purity of coasts and ports is deeply tied to the fate of the type and form of exploitation of the coast. Therefore, the present study was carried out with the purpose of collecting and integrating existing national laws in the field of construction in coastal and port areas and determining the weak points and ambiguities of existing regulations. Previous studies have been done in detail and in several publications and regulations, while existing and valid regulations throughout the world are comprehensive in the form of a book or journal. Due to the scatter of domestic publications and the absence of a comprehensive source in this study, these journals have been thoroughly and comprehensively presented as a book or journal. The design of coastal structures is designed to create harmony and uniformity in the design, construction, monitoring, and implementation of coastal structures and related projects, as well as to observe the principles, methods and technologies appropriate to the equipment and adapted to the requirements. The country is being prepared and compiled and, in addition to using the feedbacks received from the journals number 300, the guidelines and technical texts presented with the new standards of the standards and other national regulations have also been harmonized and in cases where national standards and criteria are not available, international standards should be used. The paper also attempts to make the publication available in such a way that due to the limited access to the standards and regulations and in order to expand the culture of technical knowledge and transfer it to the design and implementation of the projects, the contents of the guidelines and technical regulations necessary to provision is made to users.